Review on techno-socio-economic studies of electric vehicles in electrical energy systems - M. Nazari-Heris; S. Asadi; B. Mohammadi-Ivatloo (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2024)
Transportation electrification is a practical solution for the world's environmental, economic, and technical challenges. During the last decades, numerous studies have focused on electric vehicles (EVs) as one of the essential energy fields due to the growth rate of EV penetration into energy systems. Researchers have investigated different operation and long-term planning models of EV charging infrastructure and prediction and uncertainty-handling approaches for EV drivers’ behavior (i.e., the arrival/departure time to/from charging stations and the associated state-of-charge) as well as fixed and mobile charging stations (MCSs) and social equity access to EV charging infrastructure. This study provides a detailed analysis and discussion of the daily operation and long-term planning of EV charging stations with economic and technical aspects. Also, the prediction of EV drivers’ behavior and approaches to dealing with uncertain EV parameters are studied. Furthermore, the role of MCSs and social equity access in planning EVs’ charging station placement is investigated. The authors also assess the applications of permanent and MCSs and the social equity access to EV infrastructure. Finally, the current study discusses EVs future trends and their effect on electrical systems as future subjects of research studies.